Amyloidosis cardiomyopathy: an unforeseen cause of stroke - Lazo-Soldevilla, Marco (2022)
A 57-year-old male with a history of peripheral neuropathy and dyspnea for one year of evolution was admitted for ischemic stroke. Electrocardiographic and ultrasound studies revealed underlying hypertrophic cardiomyopathy.The electrophoretic proteinogram and immunofixation showed that it was a monoclonal gammopathy by lambda-light chains. Biopsy of gingival mucosa demonstrated and bone marrow the presence of amyloidosis. It was concluded that it was a cardiac of light chains amyloidosis secondary to monoclonal gammopathy of uncertain significance GMUS.The patient received chemotherapy but died two months after admission.